Current status of MRSA and its Resistance to Ciprofloxacin in an Urban Hospital in Dhaka City - Alam, Seemi Tasnim; Khatun, Mahbuba; Jilani, Md Shariful Alam; Haq, Jalaluddin Ashraful (Bangladesh Journal of Pathology, 2011)
DOI: http://dx.doi.org/10.3329/bjpath.v26i1.9127 BJPATH 2011; 26(1): 7-10